(untitled) (Development Service Industry Management, 2025)
The article examines managerial qualities of leaders focused on subordinates in conditions of modern socio-economic challenges. The relevance of the research is due to the transformation of the management paradigm from authoritarian approaches to human-centric models and the necessity to adapt management practices to crisis phenomena caused by the full-scale russian invasion. The aim of the research is defined as an empirical study of the essential managerial qualities of municipal enterprise leaders directed at effective interaction with subordinates. The research methodology is based on a comprehensive ascertaining experiment using adapted assessment techniques for social and emotional intelligence (SEI), motivational qualities and management style (according to R. Blake and J. Mouton’s methodology). The experimental group consisted of 30 heads of departments and divisions of a municipal enterprise aged between 30 and 65 years. The research results revealed the predominance of medium and low levels of emotional and social intelligence among the surveyed managers (40% – medium, 27% – low), which correlates with similar indicators of motivational qualities (47% – medium, 37% – low). The dominance of an authoritarian management style (30%) with a relatively high level of flexibility (56%) in adapting to different management situations was established. At the same time, indicators related to partnership approach (24%) and delegation of authority (20%) remain at an insufficient level. Analysis of the results allowed identifying the relationship between stressful conditions caused by economic instability and martial law, and the decreased ability of managers to effectively understand and manage emotions, adequately respond to the needs of subordinates and maintain their motivation. This leads to the formation of an atmosphere of distrust, limited communication and reduced team productivity. The practical significance of the research lies in substantiating the need to develop specialised programmes for the development of managerial qualities oriented towards subordinates, taking into account the specifics of functioning in crisis conditions. The obtained results can be used in formulating strategies to improve the management efficiency of municipal enterprises and developing training programmes for managers.